2012
DOI: 10.1002/jip.1366
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Coding Bias on Estimates of Behavioural Similarity in Crime Linking Research of Homicides

Abstract: This study explored whether a coding bias due to knowledge of which crimes have been committed by the same offender exists when behavioural variables are coded in serial murder cases. The study used an experimental approach where the information given to the participants (N = 60) concerning correct linkages between a number of murder series was manipulated. The participants were divided into three different groups (n = 20 in each). These three groups received correct, incorrect, or no information about the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, a recent study by Pakkanen, et al (2012), found that knowledge of the membership of an offense to a series did not appear to bias the coding of the behavioral data.…”
Section: Limitationsmentioning
confidence: 96%
“…However, a recent study by Pakkanen, et al (2012), found that knowledge of the membership of an offense to a series did not appear to bias the coding of the behavioral data.…”
Section: Limitationsmentioning
confidence: 96%
“…As well as assessing the overall accuracy of linkage decisions made, the efficacy of particular parts of the linkage process can also be assessed. Pakkanen et al's () study investigated whether prior knowledge of links between cases would create a bias as to the similarity perceived in an offender's behaviour across a series, when participants coded the information in each case as present, absent, or missing. This is an important research question for the CLA scenario where the police have already put forward an opinion as to whether they consider a group of crimes to be linked before the analyst and then conducts their analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all of the tasks in these studies are much simplified in comparison with the real‐life process as undertaken by practitioners. For example, Pakkanen et al () used edited summaries of murder case transcripts, which would not be reflective of the many case papers generated in a murder investigation. As a consequence, the results of such studies will have limited applicability to real‐world practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations